Unraveling sexual harassment's effect on employee performance: Motivation, stress, and satisfaction as key mediators - Sangadji, Suwandi S.; Sudarnice, Sudarnice; Eliyana, Anis; Fuzail, Muhammad (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
Sexual harassment has emerged as a major concern in women's workplaces and has significant implications for female employees' performance. This study aims to assess the effect of sexual harassment on the performance of Sales Promotion Girls (SPG) by considering motivation, job stress, and job satisfaction as mediating factors. Using a survey-based quantitative method, data were collected from 260 respondents from PT. Hanjaya Mandala Sampoerna and analyzed using Structural Equation Modeling (SEM) with Smart PLS.  The findings indicate that sexual harassment significantly affects job stress, work motivation, and job satisfaction among SPG. Moreover, job stress has a positive and significant effect on both work motivation and SPG performance. Sexual harassment was found to indirectly affect SPG performance through the mediating roles of job stress and work motivation. Furthermore, job satisfaction also mediates the relationship between sexual harassment and SPG performance. This study provides valuable insights for improving employee performance, particularly for SPG who experience sexual harassment. A better understanding of its impact enables companies to implement appropriate measures to reduce job stress and enhance SPG motivation, ultimately leading to increased job satisfaction. This not only fosters a safer and more positive work environment for employees but also contributes to overall productivity and SPG performance. Additionally, companies can take concrete steps to proactively prevent and address workplace sexual harassment, ensuring both the well-being and optimal performance of their SPG employees.